Several wall-associated kinases participate positively and negatively in basal defense against rice blast fungus. Issue 1 (December 2016) - Delteil, Amandine; Gobbato, Enrico; Cayrol, Bastien; Estevan, Joan; Michel-Romiti, Corinne; Dievart, Anne; Kroj, Thomas; Morel, J.-B.
Abstract Background Receptor-like kinases are well-known to play key roles in disease resistance. Among them, the Wall-associated kinases (WAKs) have been shown to be positive regulators of fungal disease resistance in several plant species.WAK genes are often transcriptionally regulated during infection but the pathways involved in this regulation are not known. In rice, theOsWAK gene family is significantly amplified compared to Arabidopsis. The possibility that severalWAKs participate in different ways to basal defense has not been addressed. Moreover, the direct requirement of riceOSWAK genes in regulating defense has not been explored. Results Here we show using rice (Oryza sativa ) loss-of-function mutants of four selectedOsWAK genes, that individual OsWAKs are required for quantitative resistance to the rice blast fungus, Magnaporthe oryz ae. While OsWAK14, OsWAK91 and OsWAK92 positively regulate quantitative resistance, OsWAK112d is a negative regulator of blast resistance. In addition, we show that the very early transcriptional regulation of the riceOsWAK genes is triggered by chitin and is partially under the control of the chitin receptor CEBiP. Finally, we show that OsWAK91 is required for H2 O2 production and sufficient to enhance defense gene expression during infection. Conclusions We conclude that the riceOsWAK genes studied are part of basal defense response, potentially mediated by chitin from fungal cell walls. This work also shows that someOsWAKs, likeOsWAK112d, may act as negative regulators of disease resistance.